If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10000 = n + -9050 Reorder the terms: 10000 = -9050 + n Solving 10000 = -9050 + n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-1n' to each side of the equation. 10000 + -1n = -9050 + n + -1n Combine like terms: n + -1n = 0 10000 + -1n = -9050 + 0 10000 + -1n = -9050 Add '-10000' to each side of the equation. 10000 + -10000 + -1n = -9050 + -10000 Combine like terms: 10000 + -10000 = 0 0 + -1n = -9050 + -10000 -1n = -9050 + -10000 Combine like terms: -9050 + -10000 = -19050 -1n = -19050 Divide each side by '-1'. n = 19050 Simplifying n = 19050
| 5p-17=-11+8p | | 5y-7x=16 | | 4=r^68 | | n^2+19n-2000=0 | | -5(2t+8)=-90 | | 4(f-7)=-16 | | 7(3x+14)+12=-19 | | 18x-10=10x+70 | | g=-4*-4 | | 6x+7y-6=0 | | 3x-15=3-5x | | 5x+7=42forx | | 10(s-10)=-146 | | s+40=0 | | 1/7(-14s)= | | -2x=8-2x | | (3x)/3=(4-1)/3 | | 4+-3a+18a^2= | | 6a(2b+5c)= | | 11x-13=3-5x | | g(x)=x*x | | 8t^4+2t^2-3=0 | | 5a^2+10a-7a+a-4+13a^2-7a+8= | | 4(3s+6)=96 | | g=(-4) | | (3x-6)(4x-3)= | | 3(2l+8)=66 | | x^2-5/2x=3 | | 5n+6=-4n+51 | | A=2(3.14)(5)(10) | | 4(a-10)=46 | | (u+5)*9=54 |